Bystanders’ Images of the Holocaust - Roma Sendyka (Miejsce)
The article is related to the visual objects produced by so-called bystanders (eyewitnesses) during the Holocaust and afterwards. Do these materials become a gesture of testimony? And if yes, when, in what circumstances, and on what conditions? If we accept them as historical evidence: will they allow access to the specific, wordless experience of the representatives of a group that—rarely analyzed and studied so far—is now is beginning to receive the attention of Holocaust researchers? In other words, will these testimonies allow us to find out something that we have not yet learned about the witnesses of Jewish suffering? And importantly, will we reclaim the ignored perspective of eyewitnesses and bystanders of the genocide through them? In the widest context: will we discover in these records, relations, meanings, emotions, and pieces of information important to understanding what happened in small communities, in the provincial territories, in Europe after 1939?